Change in Mobility after Involvement in a Cooperative: An Indication of Women’s Empowerment (KMC Journal, 2024)
Women’s participation in cooperatives has emerged as a transformative force, significantly impacting their mobility and empowerment. This study explores the impact of women’s involvement in cooperatives on their mobility, specifically focusing on the impact within the Parijat Saving and Credit Cooperative Limited in Bhaktapur District, which was purposively selected. The study focused on cooperative members who regularly saved and invested in income-generative activities through loans for at least a year. It employed the concurrent mixed methods research design. A systematic random sampling technique was employed for quantitative data collection, yielding a sample of 238 participants from various ethnic backgrounds, and the data were analyzed descriptively using cross-tabulation. Qualitative information was gathered through nine case studies, ensuring data saturation concerning changes in mobility following cooperative involvement, which were triangulated to derive findings. The findings revealed significant improvements in women’s mobility following their participation in cooperatives. Notable increases were observed in visits to new religious places, which rose from 40% to 50%, and to health centers, which increased from 48% to 85%. Particularly noteworthy was the rise in the percentage of women utilizing their vehicles, which increased from 2% before joining to approximately 20% afterward. These findings imply that cooperative involvement significantly enhances women’s mobility and independence, promoting greater access to religious and health facilities and increasing the use of personal vehicles.